2016
DOI: 10.1246/bcsj.20150296
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of Sulfoxides with Ascorbic Acid Catalyzed by NBS

Abstract: An efficient procedure to reduce sulfoxides using ascorbic acid has been developed. Using this procedure structurally diverse sulfoxides were reduced by treating with ascorbic acid in the presence of a catalytic amount of N-bromosuccinimide (NBS) at room temperature in high yields.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 37 publications
1
10
0
Order By: Relevance
“…Next, a series of hydrogenative reduction processes starting from intermediate G to CF 3 S­(O)Br were also confirmed by DFT calculations (see the Supporting Information for details). Different from the first deoxygenation of CF 3 SO 2 Cl, deoxygenation of sulfoxide does not need to overcome high energy barriers, and a classic H + /Br – system is suggested to easily realize the reduction from CF 3 S­(O)Br to CF 3 SBr as previously reported. , Meanwhile, the last unknown fluorine peak (δ = −46.09 ppm) could be identified as CF 3 SBr.…”
mentioning
confidence: 70%
See 1 more Smart Citation
“…Next, a series of hydrogenative reduction processes starting from intermediate G to CF 3 S­(O)Br were also confirmed by DFT calculations (see the Supporting Information for details). Different from the first deoxygenation of CF 3 SO 2 Cl, deoxygenation of sulfoxide does not need to overcome high energy barriers, and a classic H + /Br – system is suggested to easily realize the reduction from CF 3 S­(O)Br to CF 3 SBr as previously reported. , Meanwhile, the last unknown fluorine peak (δ = −46.09 ppm) could be identified as CF 3 SBr.…”
mentioning
confidence: 70%
“…Another approach for this kind of transformation is a halogen-induced reduction process (Scheme b). Tetracoordinate sulfur IV has enough space to be attacked by halogen, and a metal or proton can easily attack the adjacent oxygen atom, followed by deoxygenation and dehalogenation to achieve sulfur II species. By contrast, the halogen-induced deoxygenation of sulfur VI is relatively difficult; comparatively fewer research studies in this field were reported, and the mechanism of the reduction process seems to be more complex .…”
mentioning
confidence: 99%
“…On the other hand, both polymeric diselenides and disulfides are reportedly reduced by cellular reductants, although a higher sensitivity to glutathione has been reported for diselenides, which makes diselenides doubly responsive, in that they are cleaved both under oxidizing and reducing conditions (Figure B). 3) Selenide oxidation to selenoxides can be reversed with vitamin C; a similar reactivity on sulfoxides has only been recorded in the presence of sources of free radicals (N‐bromo succinimide) . 4) Less importantly, there are also some peculiarities of selenide synthetic chemistry: notably, diselenides can be used as photoinitiators, using visible light.…”
Section: Oxidation (Ros)‐responsive Materialsmentioning
confidence: 99%
“…A plausible mechanism of deoxygenation of phenylsulfenic acid (7) to thiophenol (3) in presence of HBr is shown in Scheme 7. [17] Protonation with the oxygen atom and subsequent nucleophilic attacks of bromide ion to intermediate F affords intermediate G which upon further protonation followed by the elimination of bromine and water molecules affords thiophenol (3) through intermediate H. In support of our mechanism, a control experiment for deoxygenation of phenylsulfenic acid was conducted separately using 48% HBr in acetonitrile. Thiophenol (92%) was detected within 6 h and thus the proposed deoxygenation step was verified.…”
Section: Introductionmentioning
confidence: 78%
“…A plausible mechanism of deoxygenation of phenylsulfenic acid ( 7 ) to thiophenol ( 3 ) in presence of HBr is shown in Scheme 7 [17] . Protonation with the oxygen atom and subsequent nucleophilic attacks of bromide ion to intermediate F affords intermediate G which upon further protonation followed by the elimination of bromine and water molecules affords thiophenol ( 3 ) through intermediate H .…”
Section: Introductionmentioning
confidence: 99%